Civil wind bands beyond music education: a scoping review (2010-2021) - José Cidade; João Caramelo; Alexandra Sá Costa (Ediciones Complutense, 2024)
The aim of the present study is to provide a comprehensive scoping review focused on the educational effects of active music-making participation in wind bands. This review combines mapping studies to identify the primary sources, authors, institutions, and types of evidence available in wind band research and a literature review to identify the key concepts underpinning this research domain. Based on peer-review journal literature published between 2010 and 2021, a total of 712 records were examined, resulting in 459 papers screened and 84 studies included in the analysis. Findings indicate that, in the past decade, the essential contribution to research about active music-making participation in wind bands came from Western English-speaking academic institutions based in the United States of America, Australia, the United Kingdom and Canada. The research's relevant focus was on the purposes of music education and the psychosocial and health effects of participation. Furthermore, the psychosocial effects encompassed a comprehensive set of themes, such as social bonding, community music participation, emotional well-being, and individual quality of life. Nevertheless, all these topics are closely linked to the single overarching expression of the quality of life. Other than music education, educational effects were not at the heart of the last decade of wind band research. A few gaps in the literature exist, including a lack of research concerning the educational benefits of informal and intergenerational environments of wind band practices. Equally important is the lack of research on the impacts of wind band activities on social cohesion or the inclusive intercultural development of their local communities. Lastly, there is a significant opportunity to provide up-to-date insights into the educational potential of non-school contexts and the impacts of wind band activities on supporting their places' cultural ecology.